Brachytherapy for the palliation of dysphagia owing to esophageal cancer: A systematic review and meta-analysis of prospective studies. Issue 3 (March 2017) - Fuccio, Lorenzo; Mandolesi, Daniele; Farioli, Andrea; Hassan, Cesare; Frazzoni, Leonardo; Guido, Alessandra; de Bortoli, Nicola; Cilla, Savino; Pierantoni, Chiara; Violante, Francesco Saverio; Bazzoli, Franco; Repici, Alessandro; et al.
Abstract: Background: The management of dysphagia owing to esophageal cancer is challenging. Brachytherapy has been proposed as an alternative option to stent placement. We performed a systematic review to examine its efficacy and safety in the resolution of dysphagia. Methods: Prospective studies recruiting at least 20 patients with malignant dysphagia and published up to April 2016 were eligible. The dysphagia-free survival (DFS) and adverse event rates were pooled by means of a random effect model. Results: Six studies for a total of 9 treatment arms (623 patients) were eligible for inclusion. After 1 month since treatment, the DFS rate was 86.9% [95%CI: 76.0–93.3%]; after 3 months, it was 67.2% [95%CI: 56.1–76.7%]; after 6 months, it was 47.4% [95%CI: 38.5–56.5%]; after 9 months, it was 37.6% [95%CI:30.0–45.9%]; and, finally, after 12 months, it was 29.4% [95%CI: 21.6–38.7%]. The heterogeneity between studies was high at 1-, 3- and 6-month assessment; the values of I 2 were 86.3%, 80.0% and 57.8%, respectively. The meta-regression analysis showed total radiation dose and number of fractions as the only positively influencing factors. Severe adverse event rate was 22.6% (95%CI 19.4–26.3). The main reported adverse events were brachytherapy-related stenosis (12.2%) and fistula development (8.3%). Two cases (0.3%) of deaths were reported due to esophageal perforation. Conclusion: Brachytherapy is a highly effective and relatively safe treatment option therefore its underuse is no longer justified. Further studies should investigate the optimal radiation dose and number of fractions able to achieve the highest DFS rates.